Bulk, shear and scattering attenuation beneath Hawaiian Volcanos and in the oceanic crust extending to the Aloha Cabled Observatory. Issue 1 (23rd June 2020) - Butler, Rhett
SUMMARY: Seismic attenuation is measured from a swarm of 50 earthquakes in Kīlauea volcano in 2018, associated with caldera collapse. The traverse extends at nearly constant azimuth to the saddle between Mauna Loa and Mauna Kea, continuing to Maui beneath the distal flanks of three dormant volcanos. From Maui the traverse then extends seaward to the Aloha Cabled Observatory (ACO) on the seafloor north of O'ahu. The effective attenuation is measured with respect to an ${ω ^{ - 2}}$ earthquake source model. Frequency dependent ${Q_P}$ and ${Q_S}$ are derived. The initial path is shallow and uphill, the path to Maui propagates at mid-crustal depths, and the path to ACO extends through oceanic crust. The observations of ${Q_P} \le {Q_S}$ over each traverse are modelled as bulk attenuation ${Q_K}$ . Several attenuation processes are observed, including ${Q_μ }$, ${Q_K}$, $Q\sim f$, constant Q and scattering. The observation of bulk attenuation is ascribed to contrasting physical properties between basalt and water saturated vesicles. The ratio of Q values between shallow and mid-crustal propagation is used to derive an activation energy E* for the undetermined shear attenuation mechanism. A Debye relaxation peak is fit to the ${Q_S}( f )$ and ${Q_K}( f )$ observed for the mid-crustal pathway. A prior high-frequency attenuation study near Wake Island compares well with this Hawaiian Q data set, which in general shows lower values of Q than observed for Wake.